Immunological markers of arthroplasty failure - O. V. Moskalets (Медицинская иммунология)
Periprosthetic joint infection still remains a clinical challenge since accurate definition of this condition and reliable laboratory markers have not been established yet. This study aimed to evaluate the benefit of some lymphocyte and monocyte subset determination in patients with periprosthetic joint infection and non-infectious arthroplasty failure. Thirty-four patients with chronic periprosthetic joint infection, 12 patients with non-infectious arthroplasty and 30 healthy persons were included in the study. The counts of CD3+, CD3+CD4+, CD3+CD8+, CD19+, CD3-CD16+CD56+, CD3+HLA-DR+, CD4+CD45RACD45RО+, CD4+CD45RA+ CD45RО- and CD14+ HLA-DR+ subsets in peripheral blood were assessed by flow cytometry. The assessment of the intensity of antigen expression was carried out according to mean fluorescence intensity. A significant increase in CD3+CD4+ subsets (p < 0,01) and a significant decrease in CD3-CD16+CD56+ subsets (p < 0,005) were revealed in patients with periprosthetic joint infection compared to the healthy controls. The content of CD19+ lymphocytes in these patients was significantly higher than in aseptic ones (p < 0,005); the latter group was also characterized by more pronounced increase in the number of activated T lymphocytes (CD3+HLA-DR+) compared to controls (p < 0,001). Patients with periprosthetic joint infection showed decreased “naïve” T lymphocytes (CD4+CD45RA+CD45RO-) count compared to aseptic ones (p < 0,05), and both groups showed a decrease counts compared to controls (p < 0,001). On the contrary, memory T lymphocyte (CD4+CD45RACD45RO+) count was significantly increased in both compared groups (p < 0,05). Patients with periprosthetic joint infection compared with other two groups demonstrated a significant decrease in the number of activated monocytes (CD14+HLA-DR+) and pronounced decrease in the expression intensity of this marker on cell membrane (p < 0,05 and p < 0,001, respectively). Thus, evaluation of lymphocyte and monocyte subsets, including expression of cell activation antigens could be useful as additional laboratory test in combination with other conventional methods for differentiation between periprosthetic joint infection and aseptic arthroplasty failure.